The study of attention mechanism in sound classification - Goh, Jonathan Jun Yu (Nanyang Technological University, 2021)
In modern society today, high rise building and motor vehicles exist all around us. The robust sound events detected within the environment can be heard clearly by us. However, this might not be the case for machines. I.e. Robots. Sounds captured by machines, are often filled with interference from the environment. As a result, when specific sounds such as breaking of glass or even car honks are detected, machines are unable to identify the sound event accurately.